PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM PEMBINAAN GURU - Ndanda Ambarawadi; Binti Maunah; Hikmah Eva (Jurnal Manajemen Pendidikan, 2026)
The purpose of this article is to understand the role and responsibilities of a school principal in teacher development. School principals can monitor teacher performance by conducting supervision, the results of the supervision can then be used as a source of evaluation data in improving teacher performance. The method used in this research is literature analysis, data obtained through various sources such as articles in journals and books that are related to research. The conclusion obtained is that the school principal as supervisor has a role and responsibility in carrying out teacher development or supervision, in order to achieve educational goals effectively and efficiently. The aim of teacher development by school principals is to help teachers improve and develop learning and improve the quality of work. In carrying out supervision, supervisors use individual techniques and group techniques, individual techniques namely class visits, class observations, individual meetings, and self-assessment, while group techniques include holding meetings or conferences, and holding group discussions